2020
DOI: 10.1002/adfm.201907481
|View full text |Cite
|
Sign up to set email alerts
|

Laminated Perovskite Photovoltaics: Enabling Novel Layer Combinations and Device Architectures

Abstract: High‐efficiency perovskite‐based solar cells can be fabricated via either solution‐processing or vacuum‐based thin‐film deposition. However, both approaches limit the choice of materials and the accessible device architectures, due to solvent incompatibilities or possible layer damage by vacuum techniques. To overcome these limitations, the lamination of two independently processed half‐stacks of the perovskite solar cell is presented in this work. By laminating the two half‐stacks at an elevated temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 69 publications
0
44
0
Order By: Relevance
“…It is necessary to point out that too large force can break the sample while too small force is not effective in significantly reducing the surface roughness. The present hot embossing of CsPbBr 3 film referred to a previous report on a perovskite Cs 0.1 (MA 0.17 FA 0.83 ) 0.9 Pb(I 0.83 Br 0.17 ) 3 thin film [23]. We found that the substrate temperature of 60°C can significantly decrease the surface roughness from 35 nm to 9 nm for CsPbBr 3 thin film, which is good enough to achieve the purpose of this work for experimental determination on the complex optical constants of the CsPbBr 3 thin films.…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…It is necessary to point out that too large force can break the sample while too small force is not effective in significantly reducing the surface roughness. The present hot embossing of CsPbBr 3 film referred to a previous report on a perovskite Cs 0.1 (MA 0.17 FA 0.83 ) 0.9 Pb(I 0.83 Br 0.17 ) 3 thin film [23]. We found that the substrate temperature of 60°C can significantly decrease the surface roughness from 35 nm to 9 nm for CsPbBr 3 thin film, which is good enough to achieve the purpose of this work for experimental determination on the complex optical constants of the CsPbBr 3 thin films.…”
Section: Methodsmentioning
confidence: 68%
“…The pressing of CsPbBr 3 thin films is conducted using an in-house hot-embossing machine [21][22][23]. The sample for hot embossing is placed between the upper and lower stainless steel plates and the substrate can be heated up.…”
Section: Methodsmentioning
confidence: 99%
“…Organic-inorganic perovskite materials have drawn tremendous attention for optoelectronic devices over the past decade, given their exceptional optoelectronic properties and use of low-cost precursor materials. [1][2][3][4] By compositional engineering, 5,6 optimization of the perovskite thin lm morphology, [7][8][9] and interfacial passivation, [10][11][12][13] the performance of perovskite photovoltaics was signicantly improved, reaching power conversion efficiencies (PCEs) of single-junction perovskite solar cells (PSCs) exceeding 25% in 2019. 14 This study engages with surface passivation, a strategy that is key to reduce the nonradiative recombination losses at the interface of the perovskite thin lm and the electron transport layer (ETL) or hole transport layer (HTL), thereby reducing the dark saturation current and, in turn, enhancing the open circuit-voltage (V OC ) and ll factor (FF) of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the emission spectral profile of layered perovskites was reported to be sensitive to cyclic mechanical loading in the range of tens of MPa due to the alignment of layered perovskite flakes [21]. More importantly, lamination can be achieved based on the recrystallization of perovskites, which is a promising strategy for industrial fabrication of perovskite devices since it can avoid the limitations of material choices, the issue of solvent compatibility, and device instability by forming a self-encapsulating structure [22][23][24]. Dunfield et al demonstrated a lamination process at the perovskite/perovskite interface, where two half-device stacks were independently fabricated and subsequently laminated by balancing the chemical reaction MAPbI 3 (s) + heat MA(g) + HI(g) + PbI 2 (s) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Dunfield et al demonstrated a lamination process at the perovskite/perovskite interface, where two half-device stacks were independently fabricated and subsequently laminated by balancing the chemical reaction MAPbI 3 (s) + heat MA(g) + HI(g) + PbI 2 (s) [22]. Schmager et al reported laminated perovskite solar cells using two separately processed half-stacks at the interface of the charge transport layer instead of the perovskite layer [23]. However, these two cases require either chemical reaction of specific perovskite components or functional materials.…”
Section: Introductionmentioning
confidence: 99%